DOKUMENTACJA MEDYCZNA W POSTĘPOWANIU KARNYM - Błachnio, Adam (Zeszyty Prawnicze, 2016)
Medical Records in Criminal Proceedings Summary The subject of this article is the issue of medical records in criminal proceedings. First the author discusses the main problems connected with medical records in matters relating to criminal law. He then embarks on a definition of medical records and their types from the point of view of criminal law, the ways in which they are obtained, and the principles governing the collection and keeping of documents of this kind. The author’s aim is not only to emphasise the relevance of medical records for criminal proceedings, but also to draw attention to their specific nature, and hence to their complexity and the potential they offer the judicature to obtain evidence if they are properly collected and kept.